2015
DOI: 10.1002/bmc.3468
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NF‐κB inhibitors in Qishenyiqi dropping pills for myocardial infarction treatment based on bioactivity‐integrated UPLC‐Q/TOF MS

Abstract: Qishenyiqi dropping pills (QSYQ) are a type of standardized cardiovascular multiherb medicine for the treatment of myocardial infarction (MI). Knowledge concerning the systemic identification of nuclear factor-kappa B (NF-κB) inhibitors of QSYQ is generally lacking. Therefore, it is necessary to establish an effective method to screen the bioactive components of NF-κB inhibition. In the present study, a rat model of coronary artery ligation was used to assess the cardioprotective effects of QSYQ. The electroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Diverse bioactivity-integrated UPLC-Q/TOF MS analysis systems have been established in our laboratory. An analysis system coupled with the NF-jB luciferase reporter assay system has been applied successfully to the identification of NF-jB inhibitors in many types of plant extracts and multiherb medicines (Jiang et al 2014;Gao et al 2015;Han et al 2015). Recently, our UPLC-Q/TOF MS system combined with the dual-luciferase reporter assay for intracellular calcium also successfully screened out synergistic bronchodilators from a traditional Chinese medicine (Hou et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Diverse bioactivity-integrated UPLC-Q/TOF MS analysis systems have been established in our laboratory. An analysis system coupled with the NF-jB luciferase reporter assay system has been applied successfully to the identification of NF-jB inhibitors in many types of plant extracts and multiherb medicines (Jiang et al 2014;Gao et al 2015;Han et al 2015). Recently, our UPLC-Q/TOF MS system combined with the dual-luciferase reporter assay for intracellular calcium also successfully screened out synergistic bronchodilators from a traditional Chinese medicine (Hou et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that CYT treatment decreased the levels of TNF-α, IL-1β and IL-6 in LPS-induced CMECs. An increasing number of studies have revealed that the NF-κB signaling pathway serves an important role in regulating inflammatory responses ( 16 , 24 ). NF-κB is comprised of NF-κB p50 and NF-κB p65 subunits, which are generally localized in the cytoplasm together with its inhibitor, IκB.…”
Section: Discussionmentioning
confidence: 99%